ANALISIS SISA HASIL USAHA PADA KOPERASI SIMPAN PINJAM SYARIAH BMT UGT SIDOGIRI DESA PUNGGUR KECIL - Fajriah, Nurul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this research is the rest of the business results (SHU) on Sharia Lending and Savings Cooperative BMT UGT Sidogiri desa punggur kecil. The data source of this research is from the head of the branch of sharia savings and loan cooperative BMT UGT Sidogiri desa punggur kecil. The form of research used is survey form. The place of research implementation in Sharia Lending and Savings Cooperative BMT UGT Sidogiri BMT UGT Sidogiri desa punggur kecil. The data source is the financial statements from 2013-2015. Data collection techniques used in this study are (1) Direct communication techniques with interview guides, (2) Documentary study techniques in the form of documents. The findings are the remaining results of the business (SHU) in sharia savings and loan cooperatives BMT UGT Sidogiri desa punggur kecil, each year experiencing significant. To develop the business and product of Sharia Lending and Savings Cooperative BMT UGT Sidogiri desa punggur kecil, management of Sharia Savings and Loan Cooperative BMT UGT Sidogiri also continue to evaluate and innovate the efforts and products made by Shrimp Savings and Loans Cooperative BMT UGT Sidogiri desa punggur kecil.           Keywords: SHU, Shariah Savings and Loan Cooperative BMT UGT  Sidogiri